Astrocytic GABA Accumulation in Experimental Temporal Lobe Epilepsy - Müller, Julia; Timmermann, Aline; Henning, Lukas; Müller, Hendrik; Steinhäuser, Christian; Bedner, Peter (Frontiers in Neurology, 2020)
An imbalance of excitation and inhibition has been associated with the pathophysiology of epilepsy. Loss of GABAergic interneurons and/or synaptic inhibition has been shown in various epilepsy models and in human epilepsy. Despite this loss, several studies reported preserved or increased tonic GABAA receptor-mediated currents in epilepsy, raising the question of the source of the inhibitory transmitter. We used the unilateral intracortical kainate mouse model of temporal lobe epilepsy (TLE) with hippocampal sclerosis (HS) to answer this question. In our model we observed profound loss of interneurons in the sclerotic hippocampal CA1 region and dentate gyrus already 5 days after epilepsy induction. Consistent with the literature, the absence of interneurons caused no reduction of tonic inhibition of CA1 pyramidal neurons. In dentate granule cells the inhibitory currents were even increased in epileptic tissue. Intriguingly, immunostaining of brain sections from epileptic mice with antibodies against GABA revealed strong and progressive accumulation of the neurotransmitter in reactive astrocytes. Pharmacological inhibition of the astrocytic GABA transporter GAT3 did not affect tonic inhibition in the sclerotic hippocampus, suggesting that this transporter is not responsible for astrocytic GABA accumulation or release. Immunostaining further indicated that both decarboxylation of glutamate and putrescine degradation accounted for the increased GABA levels in reactive astrocytes. Together, our data provide evidence that the preserved tonic inhibitory currents in the epileptic brain are mediated by GABA overproduction and release from astrocytes. A deeper understanding of the underlying mechanisms may lead to new strategies for antiepileptic drug therapy.